Strategies to Enhance the Efficacy of T-Cell Therapy for Central Nervous System Tumors - Upreti, Deepak; Bakhshinyan, David; Bloemberg, Darin; Vora, Parvez; Venugopal, Chitra; Singh, Sheila K. (Frontiers in Immunology, 2020)
ABSTRACT Mortality rates in patients diagnosed with central nervous system (CNS) tumors, originating in the brain or spinal cord continue to remain high despite the advances in multimodal treatment regimens, including surgery, radiation and chemotherapy. Recent success of adoptive cell transfer immunotherapy treatments using chimeric antigen receptor (CAR) engineered T cells against in chemotherapy resistant CD19 expressing B-cell lymphomas, has provided the foundation of investigating efficacy of CAR T immunotherapies in the context of brain tumor. Although significant efforts have been made in developing and translating the novel CAR T therapies for CNS tumors including glioblastoma (GBM), researchers are yet to achieve similar level of success as with liquid malignancies. In this review, we discuss strategies and considerations essential for developing robust preclinical models for translation of T cell-based therapies for CNS tumors. Some of the key consideration include route of delivery, increasing persistence of T cells in tumor environment, remodeling of myeloid environment, establishing the window of treatment opportunity, harnessing endogenous immune system, designing multiple antigen targeting T cells, and rational combination of immunotherapy with the current standard of care. Although this review focuses primary on CAR T therapies for GBM, similar strategies and consideration are applicable to all CNS tumors in general.